Barriers and facilitators to accessing healthcare for early diagnosis of prostate cancer for black men—a qualitative exploration in North-East England and Scotland - Floor Christie-de Jong; Olugbenga Samuel Oyeniyi; Lawrence Achilles Nnyanzi; Jonathan Ling; Marie K. Murphy; Judith Eberhardt; Rawand Jarrar; John Kabuye; Martin Kalemba; Kathryn A. Robb (BMC Public Health)
Abstract Introduction Prostate cancer is the most commonly diagnosed cancer in men in the United Kingdom. There are substantial inequalities in prostate cancer, with Black African and Caribbean men at least twice as likely as White men to develop prostate cancer, and twice as likely to die from it. Black men need to be aware of their elevated risk, which can encourage help-seeking behaviour leading to early diagnosis. This study aimed to investigate barriers and facilitators to accessing healthcare for early diagnosis of prostate cancer for Black men. Methods Barriers and facilitators were explored through online focus groups with Black men (n = 13) from Scotland and North-East England, who formed the Public Involvement and Community Engagement group for a larger study. Purposive and snowball sampling was used. Focus groups were audio-recorded and transcribed verbatim. Data analysis was iterative. Framework analysis was used and data were mapped onto the Integrated Screening Action Model (I-SAM). Results Participants believed Black men lack prostate cancer knowledge. Additionally, prostate cancer communication needs to use language that Black men could identify with. Participants shared a lack of trust in healthcare providers and perspectives emerged resulting from negative healthcare experiences, including experiences of racism, as barriers to accessing healthcare for early prostate cancer diagnosis. Difficulties with accessing care, including navigating the healthcare system and making appointments, as well as cultural, social and religious factors, were reported as barriers to prostate cancer health checks. Discussing intimate and sensitive issues such as prostate cancer was perceived as difficult for Black men. The involvement of community and religious leaders, along with the collectivist characteristic of the community and the belief in staying healthy for the benefit of the family, were perceived as facilitators. Conclusion Barriers to accessing healthcare for early prostate cancer diagnosis are complex and multifaceted, requiring complex solutions. Asset-based, participatory, and culturally tailored interventions have the potential to be effective in addressing barriers, and thus ultimately reduce morbidity and mortality through earlier diagnosis of prostate cancer in Black communities.